Neuroprotective effect of WIN55,212-2 against 3-nitropropionic acid-induced toxicity in the rat brain: involvement of CB1 and NMDA receptors - Maya-López, Marisol (Am J Transl Res, 2017)
The endocannabinoid system (ECS), and agonists acting on cannabinoid receptors (CBr), are known to regulate several physiological events in the brain, including modulatory actions on excitatory events probably through N-methyl-D-aspartate receptor (NMDAr) activity. Actually, CBr agonists can be neuroprotective. The synthetic CBr agonist WIN55,212-2 acts mainly on CB1 receptor. In turn, the mitochondrial toxin 3-nitropropionic acid (3-NP) produces striatal alterations in rats similar to those observed in the brain of Huntington’s disease patients. Herein, the effects of WIN55,212-2 were tested on different endpoints of the 3-NP-induced toxicity in rat brain synaptosomes and striatal tissue. Motor activity was also evaluated. The 3-NP (1 mM)-induced mitochondrial dysfunction and lipid peroxidation was attenuated by WIN55,212-2 (1 µM) in synaptosomal fractions. The intrastriatal bilateral injection of 3-NP (500 nmol/µL) to rats increased lipid peroxidation and locomotor activity, augmented the rate of cell damage, and decreased the striatal density of neuronal cells. These alterations were accompanied by transcriptional changes in the NMDA (NR1 subunit) content. The administration of WIN55212-2 (1 mg/kg, i.p.) to rats for six consecutive days, before the 3-NP injection, exerted preventive effects on all alterations elicited by the toxin. The prevention of the 3-NP-induced NR1 transcriptional alterations by the CBr agonist together with the increase of CB1 content suggest an early reduction of the excitotoxic process via CBr activation. Our results demonstrate a protective role of WIN55,212-2 on the 3-NP-induced striatal neurotoxicity that could be partially related to the ECS stimulation and induction of NMDAr hypofunction, representing an effective therapeutic strategy at the experimental level for further studies.